2018
DOI: 10.1039/c8ra00984h
|View full text |Cite
|
Sign up to set email alerts
|

Bedaquiline has potential for targeting tuberculosis reservoirs in the central nervous system

Abstract: Bedaquiline (BDQ) was administered to healthy Sprague-Dawley rats in order to determine its localisation in the brain using mass spectrometry imaging (MSI). This study shows that BDQ has the potential for targeting TB reservoirs in the CNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
(75 reference statements)
1
14
0
Order By: Relevance
“…The application of MSI to investigate small‐molecule spatial distribution was first demonstrated in 2003 following imaging of two anti‐cancer drugs, SCH 226 374 and compound A, in rat brain . Since then, a wide range of small molecules have been mapped using MSI in various biological tissues . MSI of antiretroviral drugs in various biological tissues has been done; however, there are no MSI‐related studies showing the spatial distribution of elvitegravir in biological tissues, and few studies have demonstrated the use of MSI to map tenofovir in situ .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The application of MSI to investigate small‐molecule spatial distribution was first demonstrated in 2003 following imaging of two anti‐cancer drugs, SCH 226 374 and compound A, in rat brain . Since then, a wide range of small molecules have been mapped using MSI in various biological tissues . MSI of antiretroviral drugs in various biological tissues has been done; however, there are no MSI‐related studies showing the spatial distribution of elvitegravir in biological tissues, and few studies have demonstrated the use of MSI to map tenofovir in situ .…”
Section: Resultsmentioning
confidence: 99%
“…The matrix solution was prepared by dissolving CHCA in 50% acetonitrile, 0.1% trifluoroacetic acid to make up a final concentration of 7 mg/mL. For matrix and ISTD application, a previously described standardized ImagePrep (Bruker Daltonics, Bremen, Germany) five‐cycle method was used, each cycle consisting of three steps including spraying, incubation and drying . An automated ImagePrep spraying equipment uniformly deposited the matrix onto the tissue in a form of an aerosol.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations